Identification of a non-native Cynoscion species (Perciformes: Sciaenidae) from the Gulf of Cádiz (southwestern Spain) and data on its current status - Bañón, Rafael; Arias, Alberto; Arana, Diego; Cuesta, Jose A. (Scientia Marina, 2017)
Cynoscion is a genus of fish in the family Sciaenidae from the Atlantic and Pacific American coasts that is important in recreational and commercial fisheries. Morphological analysis identifies a species inhabiting the Gulf of Cádiz (southern Spain) as the weakfish, Cynoscion regalis, a native of the northwest Atlantic. This finding is also confirmed by molecular identification using 16S and Cox1genes. Based on the examination of a previous manuscript, the assignation of this species to the spotted seatrout, Cynoscion nebulosus, is considered a misidentification. C. regalis has been reported in the area since 2011 and is now considered an established species that is distributed along the Guadalquivir River estuary and is a target of local artisanal fisheries. The pathway of introduction is unknown, but possible mechanisms are considered, of which ballast water seems to be the most plausible. A revision of non-native sciaenids also found in European waters is carried out. The ecological impact of weakfish on the local fish community is still unknown and should be object of future studies.